A comparative study of egg recognition signature mixtures in Formica ants. (1st February 2015) - Helanterä, Heikki; d'Ettorre, Patrizia
Abstract: Processing of information from the environment, such as assessing group membership in social contexts, is a major determinant of inclusive fitness. For social insects, recognizing brood origin is crucial for inclusive fitness in many contexts, such as social parasitism and kin conflicts within colonies. Whether a recognition signature is informative in kin conflicts depends on the extent of a genetic contribution into the cues. We investigated colony‐ and matriline‐specific variation in egg surface hydrocarbons in seven species of Formica ants. We show that chemical variance is distributed similarly to genetic variation, suggesting a significant genetic contribution to eggs odors in the genus. Significant among matriline components, and significant correlations between chemical and genetic similarity among individuals also indicate kin informative egg odors in several species. We suggest that egg odor surface variation could play a large role in within colony conflicts, and that a comparative method can reveal novel insight into communication of identity.